ANALISIS LAYANAN FINANCIAL TECHNOLOGY DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN MAHASISWA - Aditya Ferdiansyah; Nunuk Triwahyuningtyas (Departemen Manajemen, 2021)
This research is a quantitative research. The purpose of this study was to determine the relationship between the influence of financial technology services variables and lifestyle on student financial behavior variables. The Veterans National Development University Jakarta is the place to do research by taking the student population of the Faculty of Economics and Business. The number of samples used was 360 students who were obtained using the Slovin formula. Probability sampling with simple random sampling technique was used as the sampling method in this study and Partial Least Square (PLS) was used as the analysis technique. This study shows that financial technology services have a positive and significant effect on student financial behavior. This shows that the higher the use and benefits of financial technology services, the better the student's financial behavior will be. The results of lifestyle variables also show a positive and significant effect. So the conclusion for lifestyle variables is that even though students of the Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta have a trendy and modern lifestyle, they are able to manage their finances well.